Pengaruh Model Pembelajaran Inquiry Terbimbing Terhadap Hasil Belajar Tematik - Sherif Juniar Aryanto; Muhammad Shofiyullah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2022)
Learning is a students effort through interaction with the environment to change their behavior. In learning implementation, teachers are required to be able to understand and develop existing learning models, because the use of learning models can stimulate a learning process so that it can motivate students in their learning process, it can make students easier to understand lessons quickly, accurately, and boringless. One of the learning models that can be implemented in the scope of education is the guided inquiry learning model. This study aims to determine the effect of the guided inquiry learning model on thematic learning outcomes of fourth grade students of MI Nurul Huda Sawahan. Based on the results obtained that there is a significant difference in the fourth grade students of MI Nurul Huda, initially many students obtained learning outcomes below the minimum completeness criteria which are originally the pre-test average of 65.5% and increased by 13.5% on the post test value that is equal to 79%. The Gain Score results obtained show a Mean of 77%, which means that this guided inquiry model is effective to use, it is known that the results of the hypothesis analysis carried out are sig 0.000 so <0.005